Analysis of correlation between hydration heat release and compressive strength for blended cement pastes. (10th November 2020) - Li, Zhiping; Lu, Dagang; Gao, Xiaojian
Highlights: A quantitative approach was employed to analyze the correlation between hydration heat and strength. The fresh and hardened state of cement-fly ash-silica fume-quartz powder blended pastes were evaluated. The early hydration of blended cement was assessed experimentally. Abstract: This paper investigated the quantitative correlation relationship between hydration heat release and compressive strength in various blended cement pastes. Particularly, binary, ternary, and quaternary blends with three typical substitution materials were analysed (by mass): silica fume (0–5%), fly ash (0–30%), and quartz powder (0–20%). Techniques with the isothermal calorimetric method, strength measurement and scanning electron microscopy (SEM) were used to analyse the initial and hardened stages of blended cementitious pastes. Then, linear relationships were evaluated by using the Pearson statistical method. The results showed that adding substitution materials significantly changes release peak value and cumulative hydration heat, but peak time does not fluctuate evidently. Cumulative hydration heat of binary, ternary and quaternary blended cement pastes reduced to varying degrees compared with reference cement. The compressive strength of quaternary blends substantially decreased at 28 d when the substitution of cement exceeds 45%. Binary, ternary, and quaternary cement mixtures exhibited a strong linear correlation between cumulative hydration heat (hydration exothermic peak) and 28-day compressive strength at some special conditions, and the Pearson correlation coefficient of 0.8–1. Hence, the prediction of 28-day compressive strength from measuring hydration heat with isothermal calorimetric is valid for the particular blended mixture employed in this study.